Assessment of aquatic ecosystem status using macrophyte species as key tools indicator for heavy metal pollution - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Baharuddin, Zainul Mukrim; Hashim , Khairusy Syakirin Has-Yun; Hasni, Shah Irani (Universiti Teknologi Malaysia, 2015)
Aquatic plants or macrophytes are beneficial to fresh water bodies because they produce oxygen, which assists with overall fresh water bodies functioning, and provide food and shelter for aquatic living organisms. A lack of aquatic plants in a freshwater bodies system where they are expected to occur may suggest a reduced population of macro and micro fauna. In addition, the absence of macrophytes may also indicate water quality problems as a result of excessive turbidity, herbicides, or salinization. However, an over abundance of macrophytes can result from high nutrient levels and may interfere with freshwater bodies processing, recreational activities and detract from the aesthetic appeal of the system. In this study, sixteen water samples were collected from four different places (Selangor, Perak, Pahang and Kelantan) where six different macrophytes species were abundance and dominant. All the water samples were analyzed by using Atomic absorption spectroscopy (AAS) for six types of heavy metals which are iron (Fe), lead (Pb), copper (Cu), zinc (Zn), nickel (Ni) and manganese (Mn). All six different macrophytes species which are Eichhorniacrassipes, Hydrillaverticillata, Cabombafuscata, Salvinianatans, Nelumbonuciferaand Pistiastratiotesexhibiting highly significant differences (P< 0.0001) between aquatic plant species widespread, locations and the heavy metals content. This clearly demonstrates that freshwater environment with abundance of invasive macrophyte species can have an important influence and indication on the accumulation of heavy metals content. The importance of the interaction components emphasises that the changes in heavy metals composition are complex and the responses are not consistent across all aquatic plant species. Examination of the summarised data revealed that, of the 6 macrophyte species analysed at all different locations, all exhibits as potential ecological indicator for unhealthy aquatic ecosystems or as phytoindicator for heavy metal contaminants either at low or high level contamination. Therefore, macrophyte is an effective tool in responding heavy metal in low level environmental contamination that might otherwise be difficult to detect.